Will Digital Inclusive Finance Make Economic Development Greener? Evidence From China - Li, Guangqin; Fang, Xubing; Liu, Maotao (Frontiers in Environmental Science, 2021)
This paper aimed to accurately assess the driving effect of digital inclusive finance (DIF) on green economic growth, better implement DIF-related policies, and promote the development of green economy. Based on the urban panel data from 2011 to 2018 and the DIF index, this paper investigates the impact of DIF on economic green development and its internal mechanism. The results show that there is a significant positive U-shaped nonlinear relationship between DIF and green development. Through the robustness test of the threshold model, instrumental variable model (IV), and system generalized method of moments (SYS-GMM) model, the results are still valid. The mechanism research shows that the DIF can indirectly promote China’s green development by the coagglomeration degree of producer services and optimize and upgrade industrial structure. This study provides policy implications for developing countries around the world to achieve green development by promoting the DIF level.